The Role of Whatsapp Business in Increasing Consumer Engagement by Implementing Dewa Eka Prayoga Marketing Techniques - Sayudin Sayudin; Kartono Kartono; Aang Curatman (Journal of World Science, 2024)
The development of digital communication technology has changed the marketing paradigm, with WhatsApp Business becoming one of the popular platforms companies use to interact with customers. Effective marketing techniques such as those developed by Dewa Eka Prayoga, a well-known practitioner in the field of marketing, have become a concern in efforts to increase consumer engagement. This research aims to investigate the role of WhatsApp Business in increasing consumer engagement by applying Dewa Eka Prayoga marketing techniques. This research focuses on understanding the extent to which WhatsApp Business and Dewa Eka Prayoga's marketing techniques can increase consumer interaction and engagement. This research uses a quantitative research method with data collection using a questionnaire. The respondents were randomly selected from the target population of WhatsApp Business users who have used the Dewa Eka Prayoga marketing technique. The questionnaire was structured based on consumer involvement dimensions and the effectiveness of marketing techniques, and it was analyzed using descriptive and inferential statistical methods. This research analysis shows that WhatsApp Business significantly increases consumer engagement when applied with the Dewa Eka Prayoga marketing technique. The high level of interaction between companies and consumers via WhatsApp Business positively influences consumer perceptions, as well as increases the level of consumer satisfaction and loyalty. This research concludes that WhatsApp Business is an effective tool for increasing consumer engagement when used together with Dewa Eka Prayoga's marketing techniques. Companies can use this platform to strengthen consumer relationships, expand marketing reach, and increase customer loyalty.